2008
DOI: 10.1266/ggs.83.77
|View full text |Cite
|
Sign up to set email alerts
|

Mosaic genealogy of the Mus musculus genome revealed by 21 nuclear genes from its three subspecies

Abstract: Patterns of genetic variation provide insight into the evolutionary history of a species. Mouse (Mus musculus) is a good model for this purpose. Here we present the analysis of genealogies of the 21 nuclear loci and one mitochondrial DNA region in M. musculus based on our nucleotide sequences of nine inbred strains from three M. musculus subspecies (musculus, domesticus, and castaneus) and one M. spicilegus strain as an outgroup. The mitochondrial DNA gene genealogy of those strains confirmed the introgression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 53 publications
4
14
0
Order By: Relevance
“…This result agrees with the phylogenetic history of house mice. High levels of phylogenetic discordance among gene trees indicate that the ancestor of M. m. musculus and M. m. castaneus diverged rapidly from the M. m. domesticus lineage (Tucker et al 1989;Prager et al 1996Prager et al , 1998Lundrigan et al 2002;Goios et al 2007;Geraldes et al 2008;Liu et al 2008;White et al 2009;Keane et al 2011). The short internal branch leading from the root to the most recent common ancestor of M. m. musculus and M. m. castaneus provided little time for derived-derived incompatibilities (Orr 1995) to evolve.…”
Section: Discussionmentioning
confidence: 99%
“…This result agrees with the phylogenetic history of house mice. High levels of phylogenetic discordance among gene trees indicate that the ancestor of M. m. musculus and M. m. castaneus diverged rapidly from the M. m. domesticus lineage (Tucker et al 1989;Prager et al 1996Prager et al , 1998Lundrigan et al 2002;Goios et al 2007;Geraldes et al 2008;Liu et al 2008;White et al 2009;Keane et al 2011). The short internal branch leading from the root to the most recent common ancestor of M. m. musculus and M. m. castaneus provided little time for derived-derived incompatibilities (Orr 1995) to evolve.…”
Section: Discussionmentioning
confidence: 99%
“…In the analyses of complex traits in wild-derived strains, we identified a marked diversity of phenotypes among strains [12,17,24,29]. The phenotypic diversity is believed to be a result of genetic diversity among wild-derived strains, as shown by several studies on genomic polymorphisms of these strains [17,18,20,23,27]. As each wild-derived strain has a different evolutionary history, we can expect a unique haplotype in each strain [16].…”
Section: Proposal Of a New Approach To Elucidate Complex Traitsmentioning
confidence: 95%
“…Recent parsimony analysis of SSLP in 54 CIS indicated that C57-derived strains are apparently distantly related to the other CIS group [28]. Liu et al [9] have investigated mouse genome genealogy using 21 nuclear genes in CIS and WIS. Two genes of C57BL/10, Dfy (Duffy-like blood group) on chromosome 1 and Tnf (tumor necrosis factor) on chromosome 17 were MUS type. BAC-end sequence-SNP analysis of the MSM strain demonstrated that around 6% of its genome is similar to that of C57BL/6 [1].…”
Section: Unique Phylogenetic Status Of the C57bl Strain In The Phylogmentioning
confidence: 99%